Immigration Law: Analysis of The Application of Criminal Law Towards Immigration Permit Abuse in Bima - Wardin, Wardin; Syamsuddin, Syamsuddin; Ihlas, Ihlas (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The misuse of immigration permits constitutes a legal violation that can disrupt public order, threaten national security stability, and undermine the integrity of a country's immigration system. This study aims to comprehensively analyze the application of criminal law to the misuse of immigration permits, whether committed by foreign nationals or domestic actors. The primary focus is on evaluating the effectiveness of criminal law norms within the Immigration Law and their implementation in practice, including both juridical and non-juridical obstacles faced by law enforcement authorities. The research employs a normative juridical method with statutory and conceptual approaches, complemented by case studies from several relevant court decisions. Data were collected through literature review and analyzed qualitatively. The findings reveal a gap between established legal norms and their implementation in the field. Law enforcement is often hindered by weak inter-agency coordination, limited human resources, and the suboptimal use of legal instruments to create deterrent effects. These findings highlight the urgency of reformulating clearer criminal law norms and strengthening the institutional capacity of immigration authorities and law enforcement agencies. The novelty of this research lies in its integrative approach, bridging immigration law and criminal law, which are often applied in a sectoral manner. This study is expected to contribute scientifically to improving immigration policy and enhancing the effectiveness of criminal law enforcement against immigration violations in Indonesia.. [Penyalahgunaan izin keimigrasian merupakan bentuk pelanggaran hukum yang dapat mengganggu ketertiban umum, mengancam stabilitas keamanan nasional, dan melemahkan integritas sistem keimigrasian suatu negara. Penelitian ini bertujuan untuk menganalisis secara komprehensif penerapan hukum pidana terhadap praktik penyalahgunaan izin keimigrasian, baik oleh warga negara asing maupun pelaku domestik. Fokus utama terletak pada evaluasi efektivitas norma hukum pidana dalam Undang-Undang Keimigrasian serta implementasinya dalam praktik, dengan menyoroti berbagai kendala yuridis dan nonyuridis yang dihadapi aparat penegak hukum. Metode yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan konseptual, serta didukung oleh studi kasus dari beberapa putusan pengadilan yang relevan. Data dikumpulkan melalui studi pustaka dan dianalisis secara kualitatif. Hasil penelitian menunjukkan adanya kesenjangan antara norma hukum yang berlaku dengan realitas implementatif di lapangan. Penegakan hukum seringkali terhambat oleh lemahnya koordinasi antar lembaga, keterbatasan sumber daya manusia, serta belum optimalnya instrumen hukum dalam menimbulkan efek jera. Oleh karena itu, perlu dirumuskan norma hukum pidana yang lebih operasional dan penguatan kelembagaan dalam sistem keimigrasian. Kebaruan dari penelitian ini terletak pada pendekatan integratif antara hukum keimigrasian dan hukum pidana yang selama ini cenderung diterapkan secara sektoral. Penelitian ini diharapkan dapat memberikan kontribusi ilmiah dalam pembaruan kebijakan keimigrasian dan peningkatan efektivitas penegakan hukum terhadap pelanggaran keimigrasian di Indonesia.]